2022
DOI: 10.1186/s12877-022-03030-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting cultural change towards dementia friendly communities: a multi-level intervention in Japan

Abstract: BackgroundEffective strategies to develop dementia-friendly communities (DFCs) are needed in aging societies. We aimed to propose a strategy to develop DFCs from a Japanese perspective and to evaluate an intervention program that adopted the strategy.MethodsThis study implemented a multi-level intervention that emphasized nurturing community social capital in a large apartment complex in the Tokyo metropolitan area in 2017. We offered an inclusive café that was open for extended hours as a place to socialize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In Japan, the frequency and duration of previously predominant community activities such as neighborhood associations and festivals have been reduced. It has been suggested that alternative volunteer groups and community salons may serve as a basis for DFCs (Tsuda et al., 2022). Another study suggests that interventions using a health promotion approach may have merit in creating DFCs (Kawachi & Berkman, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the frequency and duration of previously predominant community activities such as neighborhood associations and festivals have been reduced. It has been suggested that alternative volunteer groups and community salons may serve as a basis for DFCs (Tsuda et al., 2022). Another study suggests that interventions using a health promotion approach may have merit in creating DFCs (Kawachi & Berkman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…DFCs are communities where people with dementia feel understood, respected, and supported by those around them and feel more confident in participating in and contributing to social activities. In Japan, policies aimed at promoting successful DFCs, as well as activities organized by companies, nonprofit organizations, and community organizations, have been gradually expanding and spreading awareness since the 2010s (Tsuda et al., 2022). Our research team has been conducting epidemiological and action research since 2016, establishing a community center within the Takashimadaira housing complex in Itabashi ward, Tokyo, to build an urban model of DFCs (Okamura et al., 2020; Ura et al., 2021).…”
Section: Introductionmentioning
confidence: 99%